2001
DOI: 10.1521/suli.31.3.342.24252
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Suicide Prevention in Front‐Line Health Staff

Abstract: A questionnaire assessing attitudes toward suicide prevention was constructed and shown to have satisfactory reliability and internal consistency. The determinants and distribution of these attitudes were investigated in four groups of health professionals who are in contact with suicidal patients: general practitioners, accident and emergency nurses, psychiatrists in training, and community psychiatric nurses. Attitudes toward suicide prevention were shown to differ significantly between professional groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 8 publications
5
145
3
Order By: Relevance
“…Here the findings were inconsistent. Whilst two papers found that more experienced staff had more positive attitudes towards mental health presentations (Commons-Treloar et al 2008, McAllister et al 2002, two other papers (Friedman et al 2006, Herron et al 2001 reported that years of experience was weakly correlated with more negative attitudes.…”
Section: Staff Perspectivesmentioning
confidence: 99%
“…Here the findings were inconsistent. Whilst two papers found that more experienced staff had more positive attitudes towards mental health presentations (Commons-Treloar et al 2008, McAllister et al 2002, two other papers (Friedman et al 2006, Herron et al 2001 reported that years of experience was weakly correlated with more negative attitudes.…”
Section: Staff Perspectivesmentioning
confidence: 99%
“…Antipathy for the self-harming patient and their care remains a significant barrier to improving care in the health care arena (Patterson et al, 2007a). There is a paucity of literature available regarding attitude change towards this vulnerable population (Herron et al, 2001) especially in Ireland.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to communicate the importance of psychosocial assessment and to ensure that assessments are conducted appropriately, ED staff may require specific training in how to deal with patients following self-harm 8 13 19 22. Training should also address any negative attitudes staff have towards self-harm as this can have a negative impact on assessment and treatment 2 15 23…”
Section: Strengths and Limitationsmentioning
confidence: 99%